When the bough breaks - Clarke, Amy Catherine, author; Lundberg, Thomas R., advisor; Reid, Louann, committee member; Coronel, Patricia D., committee member; Voss, Gary Wayne, committee member (Colorado State University. Libraries, 1997)
To view the abstract please see the full text of the document.
Keywords: Installations (Art)